2009
DOI: 10.1103/physrevb.80.195323
|View full text |Cite
|
Sign up to set email alerts
|

Generation of terahertz radiation by bulk and surface optical rectification from crystal planes of arbitrary orientation

Abstract: Generation of terahertz radiation by bulk and surface optical rectification from Generation of terahertz radiation by bulk and surface optical rectification from crystal planes of arbitrary orientation crystal planes of arbitrary orientation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…In some materials, for example GaAs, under normal experimental conditions the bulk term largely accounts for the data, although including the surface term as well provides a more satisfactory fit [8]. For other materials, such as GaAsBi epilayers, the surface term plays a significant role [10].…”
Section: Invited Articlementioning
confidence: 98%
See 1 more Smart Citation
“…In some materials, for example GaAs, under normal experimental conditions the bulk term largely accounts for the data, although including the surface term as well provides a more satisfactory fit [8]. For other materials, such as GaAsBi epilayers, the surface term plays a significant role [10].…”
Section: Invited Articlementioning
confidence: 98%
“…Recently, a general theory has been given for zinc-blende crystals [8] and compared in detail to the previous work in the literature [9]. We show schematically in Fig.…”
Section: Optical Rectification (Or)mentioning
confidence: 99%
“…The azimuthal angle dependence shows most of the radiation is originating in OR, consistently with a recent general model of OR. 11,12 To conclude, we have demonstrated that irradiating nanoporous membranes of ͑111͒ InP with heavy noble-gas ions enhances terahertz emission. Systematic investigation of the dependence of the generated terahertz electric field on excitation pump power, in-plane magnetic field, and azimuthal angle indicate that the underlying physical mechanism is OR rather than TC flow.…”
Section: Figmentioning
confidence: 99%
“…Over a complete ͑360°͒ rotation we observe a 3 dependence, as expected for a ͑111͒ face. 11 In Fig. 4 we only show the behavior over the one-third ͑120°͒ repeat unit.…”
Section: Figmentioning
confidence: 99%
“…This has led to a generalized theory for the azimuthal angle dependence of optical rectification, in which comparisons between theory and experiment were made for 11N GaAs crystals [1]. It was found that the emission was a mixture of both bulk (second order) and surface (third order) effects and that the surface field was of roughly the same magnitude but opposite direction depending on whether one was illuminating the A or B face of the crystal (A refers to the Ga rich surface and B the As rich surface).…”
Section: Introductionmentioning
confidence: 99%